Intracranial and intradural nasal polyposis after iatrogenic skull base defect: A case report. (4th May 2017) - Holzer, Martin; Thon, Niklas; Stelter, Klaus; Rachinger, Walter; Betz, Christian Stephan
Abstract: We report the first case of an intracranial and intradural nasal polyposis occurring in a close topographical relation to a previous, iatrogenic anterior skull base defect. The tumour was resected and the skull base defect was closed transnasally by an interdisciplinary team. The histopathological report confirmed recurrent polyposis.